QFuego-Patagonia v1: a comprehensive glacier-related dataset for Patagonia and Tierra del Fuego, South America - Farías-Barahona, David (PANGAEA, 2025)
We present QFuego-Patagonia v1 (https://qfuego-patagonia.org/), a free glacier-related geographical information system (GIS) package covering Patagonia and Tierra del Fuego. It includes essential geospatial glacier data across five disciplines (Glaciology, Geophysics, Atmosphere, Bathymetry, and Glacial Geology and Geomorphology). Our goal is to foster interdisciplinary research and collaboration, enhancing our understanding of glacier dynamics and their broader climate implications. Future plans involve integrating other disciplines and creating consensus estimates for specific fields. This initiative aims to establish an advanced glacier data repository, summarizing knowledge and supporting high-quality research emergence.
Keywords: Patagonia; Patagonian Ice Sheet; Tierra del Fuego